Three-stage pH-switchable organic chromophores with large nonlinear optical responses and switching contrasts - Van Bezouw, Stein; Koo, Min Jeong; Lee, Seung Chul; Lee, Seung Heon; Campo, Jochen; Kwon, O. Pil; Wenseleers, Wim (Chemical Communications, 2018)
Three-stage pH-switchable organic second-order nonlinear optical (SO NLO) chromophores are synthesized and characterized by wavelength-dependent linear and nonlinear spectroscopy. The chromophores exhibit huge SO NLO responses in their “on” stages, and large switching contrasts between adjacent stages in both SO NLO response and fluorescence quantum yield, with moreover different “on/off” sequences for closely related compounds.